Comparative evaluation of different soybean meal and the replacement using peanut, rapeseed and fish meal for broilers . - Budi Tangendjaja; I.A.K Bintang (Jurnal Ilmu Ternak dan Veteriner, 1996)
Two feeding experiments have been conducted to test the different sources of soybean meal (local, India, USA) and the partial substitution with peanut meal (10%), rapeseed meal (5%) and fish meal (5%) in the diet for broiler. The first feeding experiment was carried out on broiler starter for 4 weeks in wire cages . Twelve rations in factorial design (3 x 4) were conducted using 6 birds/cage and replicated 6 times . Birds fed India soybean meal had significantly less body weight (1,000 g) than those fed local or USA soybean meals (1,037 and 1,023 g, respectively) . Partial substitution with peanut, rapeseed or fish meal did not affect body weight, feed consumption or feed/gain ratio . The average consumption and feed/gain were 1,535 g and 1,569, respectively . In second experiment, one thousand five hundred broiler chicks were allocated in 6 dietary treatments in factorial design (3 x 2) . Factor one was different sources of soybean meal (local, India and USA) and factor two was the inclusion of peanut meal at 0 and 10%. Birds were kept on litter system for 6 weeks . Each treatment used 5 replicates and 50 birds/replicate . The results show no effect of the treatment to any parameter measured . Body weight of bird fed local, India and USA soybean meal were 1,662, 1,641 and 1,669 g and feed/gain were 2 .043, 2 .051 and 2.035, respectively . Cost analysis indicates that ration uses local soybean meal gives a higher cost than those of India and USA soybean meals.   Key words : Soybean meal, peanut meal, rapeseed meal, fish meal, broiler